Acute invasive hemodynamic effects of percutaneous mitral paravalvular leak closure. Issue 5 (4th May 2017) - Lloyd, James W.; Rihal, Charanjit S.; Reeder, Guy S.; Nishimura, Rick A.; Eleid, Mackram F.
Abstract : Objectives: The aim of this study was to demonstrate the physiologic effects of percutaneous mitral paravalvular leak (PVL) closure through pre‐ and post‐closure left and right heart catheterization. Background: Mitral PVL represents a significant source of morbidity and mortality following mitral valve repair and replacement. Although percutaneous PVL closure is an effective treatment with improvements in symptoms and mortality, data regarding the acute hemodynamic effects of such closure are lacking. Methods: Consecutive patients with clinically significant heart failure and/or hemolysis attributed to mitral PVL underwent percutaneous mitral PVL closure with pre‐ and post‐procedural right and left heart catheterization. Hemodynamic measurements of cardiovascular function obtained in this manner were compared and stratified according to pre‐ and post‐procedural echocardiographic severity of PVL. Results: Twenty‐four patients (age 68 ± 9.4 years, 75% male) underwent percutaneous mitral PVL closure. Significant improvements were found in left atrial pressure (LAP) (mean LAP lowered from 21 ± 4 to 19 ± 3 mm Hg, P  = 0.005), pulmonary artery pressure (PAP) (mean PAP lowered from 36 ± 11 to 33 ± 9, P  = 0.04), and cardiac index (increased from 2.8 ± 0.8 to 3.0 ± 0.7 L/min/m 2, P  = 0.01). Left atrial v‐wave reduction of 20% was associated with ≤ mild residual PVL by transesophageal echocardiography ( P  = 0.09). Conclusions: Percutaneous mitral PVL closure is associated with significant reductions in LAP and PAP and an increase in cardiac index. These hemodynamic effects underlie the clinical benefits of PVL closure and may be a useful tool for intraprocedural guidance. © 2017 Wiley Periodicals, Inc.